2005
DOI: 10.2527/2005.8351179x
|View full text |Cite
|
Sign up to set email alerts
|

Intake, digestion, and N metabolism in steers fed endophyte-free, ergot alkaloid-producing endophyte-infected, or nonergot alkaloid-producing endophyte-infected fescue hay1

Abstract: A digestion and N balance trial was conducted to compare effects of traditional endophyte-infected (E+), endophyte-free (E-), and nontoxic endophyte infected (NE; MaxQ; Pennington Seed, Inc., Madison, GA) Jesup tall fescue (Festuca arundinacea Schreb.) hay on digestion and N retention in steers. Hay composition (DM basis) was as follows: E+ (10.8% CP, 59.9% NDF, and 29.4% ADF), E- (11.8% CP, 58.5% NDF, and 28.4% ADF), and NE (11.6% CP, 58.6% NDF, and 28.3% ADF). Eight Polled Hereford steers (initial BW 240 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…Apparent DM (P = 0.48), ADF (P = 0.62), and CP (P = 0.89) digestibilities were not different between treatment groups (Table 2), which agrees with Stamm et al (1994), although it should be noted that DM digestibility was numerically 4 percentage units greater for E− than for E+. Matthews et al (2005) reported lower DM, ADF, and CP digestibilities in animals consuming an endophyte-infected diet compared with those on an endophyte-free diet. The difference in the effect of ergovaline on nutrient digestibilities could be related to the quality of the different feeds.…”
Section: Digestive and Physiological Parametersmentioning
confidence: 90%
See 2 more Smart Citations
“…Apparent DM (P = 0.48), ADF (P = 0.62), and CP (P = 0.89) digestibilities were not different between treatment groups (Table 2), which agrees with Stamm et al (1994), although it should be noted that DM digestibility was numerically 4 percentage units greater for E− than for E+. Matthews et al (2005) reported lower DM, ADF, and CP digestibilities in animals consuming an endophyte-infected diet compared with those on an endophyte-free diet. The difference in the effect of ergovaline on nutrient digestibilities could be related to the quality of the different feeds.…”
Section: Digestive and Physiological Parametersmentioning
confidence: 90%
“…Early work typically classified treatments as infected vs. noninfected tall fescue with no analysis for ergopeptide alkaloid levels (Fiorito et al, 1991;Paterson et al, 1995). When alkaloids were tested, the treatment levels of ergopeptides varied greatly, ranging from 0.12 mg/kg of ergovaline (Matthews et al, 2005) to 2.43 mg/kg of ergovaline (Aldrich et al, 1993) in the high treatments. Higher ambient temperatures and heat stress can cause a greater change in rectal temperature for animals consuming endophyte-infected diets when compared with endophyte-free diets (Hannah et al, 1990;Gadberry et al, 2003).…”
Section: Digestive and Physiological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the 5‐d collection, the composite frozen samples were oven‐dried (55°C), weighed for dry matter (DM) determination, ground in a Wiley mill to pass a 1‐mm screen, thoroughly mixed, subsampled, and stored at room temperature until analyzed. Total urine was collected each of the 5 d for N balance determination as described by Matthews et al (2005), except 6 M acetic acid was used to maintain urine pH below 6.0.…”
Section: Methodsmentioning
confidence: 99%
“…The reported fiscal impact of ergot alkaloids is in the tens and hundreds of millions of dollars. The greatest clinical and financial impact is in the beef industry, with cattle being affected with a number of pathologies (Burfening 1973;Peters et al 1992;Porter and Thompson 1992;Aldrich et al 1993;Dyer 1993;Porter 1993;Hill et al 1994Hill et al , 2000Oliver et al 1994;Cheeke 1995;Schneider et al 1996;Stuedemann et al 1998;Schultze et al 1999;Schnitzius et al 2001;Parish et al 2003;Matthews et al 2005;Realini et al 2005;Wang et al 2009). The symptoms in cattle include increased respiration rates, increased rectal temperatures, salivation, nervousness and rough hair coats, decreased weight gains and decreased overall performance in beef steers (Hoveland 1993).…”
Section: Introductionmentioning
confidence: 99%